Blood-Based Non-Invasive Tests of Hepatic Fibrosis in Autoimmune Hepatitis: Application among Selected Patients Leads to Higher Accuracy - Marco Ferronato; Marco Lenzi; Paolo Muratori; Luigi Muratori (Gastroenterology Insights, 2022)
Background. Assessment of liver fibrosis is essential to guide treatment in autoimmune hepatitis (AIH), but non-invasive tests (NITs) showed poor accuracy. Our study aims to evaluate the performance of NITs among different AIH presentations. Methods. Monocentric retrospective study among 122 AIH patients. NITs were compared to histological grading of liver fibrosis. We performed an accuracy analysis among acute (jaundice and/or transaminases > 10 times upper limit of normal) and non-acute patients. Results. A significant difference in the distribution of NIT values for each Ishak stage was found for spleen-diameter-to-platelet-count ratio (SD/PC) (p < 0.001), fibrosis-4-score (FIB-4) (p = 0.002), AST-to-ALT ratio (AAR) (p = 0.002), red-blood-cell-width-distribution-to-platelet-count ratio (RDW/PC) (p = 0.008) and AST-to-platelet-count ratio (APRI) (p = 0.029). The AUC for advanced fibrosis of SD/PC, FIB-4, RDW/PC, APRI and AAR were, respectively, 0.814, 0.770, 0.768, 0.708 and 0.694. The AUC of SD/PC, FIB-4 and APRI in non-acute subgroup were 0.902, 0.834 and 0.758, while in acute patients they were 0.754, 0.724 and 0.716. RDW/PC and AAR weren’t different among the two subgroups. Conclusions. For SD/PC, FIB-4 and APRI, diagnostic accuracy is higher in patients with non-acute presentation. In this context, SD/PC and FIB-4 showed an overall performance that could be of interest in clinical practice alongside other non-invasive techniques.